The Effect Of Work Life Balance And Work Stress On Performance With Job Satisfaction As Intervening Variables At The Office Of Theministry Of Religion, Selatan Tapanuli Regency - Hilman, Hilman; Ronny Edward, Yusuf; Faris, Salman (International Journal of Science, Technology & Management, 2022)
This study aims to analyze the effect of work life balance and work stress on performance with job satisfaction as a moderating variable for employees at the Ministry of Religion Office of South Tapanuli Regency. The population in this study were 58 people. The technique used in sampling is purposive sampling. The data analysis tool uses SPSS. The results of the analysis show that Work Life Balance has a positive and significant effect on employee job satisfaction at the Office of the Ministry of Religion of South Tapanuli Regency. Job stress has a positive and significant effect on job satisfaction at the Office of the Ministry of Religion of South Tapanuli Regency. Work Life Balance has a positive but significant effect on performance at the Office of the Ministry of Religion of South Tapanuli Regency. Job stress has a positive and significant effect on performance at the Office of the Ministry of Religion of South Tapanuli Regency. Job satisfaction has a positive but not significant effect on performance at the Office of the Ministry of Religion of South Tapanuli Regency. The direct effect of Work Life Balance on performance is greater than the indirect effect of Work Life Balance on performance. The direct effect of work stress on performance is smaller than the indirect effect of work stress on performance.